Description and Evaluation of the MIT Earth System Model (MESM). (3rd August 2018) - Sokolov, Andrei; Kicklighter, David; Schlosser, Adam; Wang, Chien; Monier, Erwan; Brown‐Steiner, Benjamin; Prinn, Ronald; Forest, Chris; Gao, Xiang; Libardoni, Alex; Eastham, Sebastian
Abstract: The Massachusetts Institute of Technology Integrated Global System Model (IGSM) is designed for analyzing the global environmental changes that may result from anthropogenic causes, quantifying the uncertainties associated with the projected changes, and assessing the costs and environmental effectiveness of proposed policies to mitigate climate risk. The IGSM consists of the Massachusetts Institute of Technology Earth System Model (MESM) of intermediate complexity and the Economic Projections and Policy Analysis model. This paper documents the current version of the MESM, which includes a two‐dimensional (zonally averaged) atmospheric model with interactive chemistry coupled to the zonally averaged version of Global Land System model and an anomaly‐diffusing ocean model. Key Points: Climate sensitivity and rate of ocean heat uptake of the MIT Earth System Model can be varied over wide ranges to address uncertainty Computational efficiency of the Model allows us to run large ensembles of simulations for robust uncertainty quantification The inclusion of an atmospheric chemistry model allows us to perform emission‐driven simulations and evaluate impacts of different policies on future climate